Mechanics and Energetics of Soil Penetration by Earthworms and Plant Roots: Higher Rates Cost More. Issue 8 (10th August 2017) - Ruiz, Siul; Schymanski, Stanislaus J.; Or, Dani
Abstract : Core Ideas: We quantified mechanical differences between earthworms and roots using penetration rates. Mechanical modeling was justified by direct imaging of both plant roots and earthworms. We validated model predictions with rate‐controlled miniature cone penetrometer experiments. Earthworm burrows are dominantly formed through mechanical processes, not ingestion. We outline mechanical and energetic limitations for a range of water contents. We quantified the mechanics and energetics of soil penetration by burrowing earthworms and growing plant roots considering different penetration rates and soil mechanical properties. The mechanical model considers cavity expansion by cone‐like penetration into a viscoelastic soil material in which penetration rates affect the resulting forces and hence the mechanical energy required. To test the predicted penetration rate effects on forces and energetics, we conducted rate‐controlled cone penetration experiments across rates ranging from 1 to 200 μm s −1 to determine the mechanical resistance forces for cone geometries similar to plant roots and earthworms. These measurements also enabled inverse estimation of soil rheological parameters that were in good agreement with literature values for similar soils and water contents. The results suggest that higher soil penetration rates typical for earthworm activity (about 200 μm s −1 ) may significantly increase resistance forces and energy expenditure by up to threefold relative to slower penetration rates of plant roots (0.2 μm s −1 ) for similar soil properties and geometries. Another important mechanical difference between earthworms and roots is the radial pressures that earthworms' hydro‐skeleton exerts (<230 kPa), whereas plant roots may exert radial pressures exceeding 1 MPa. These inherent differences in burrowing rates and expansion pressures may significantly extend the range of conditions suitable for root growth in drier and compacted soil compared to earthworm activity. Results suggest that the mechanical energy costs of soil bioturbation under agricultural intensification and drier climate could greatly increase the energetic costs of these ecologically important soil structure‐forming bioprocesses.